MO524CALCIMIMETIC ADHERENCE AND PREFERENCE IN THE MANAGEMENT OF SECONDARY HYPERPARATHYROIDISM IN EUROPE: A PILOT STUDY. (29th May 2021) - Louie, Karly; Nduka, Chidozie; Taylor, Jo; Hall, Matthew; Aucella, Filippo; Artero, Josep; Ureña, Pablo; Labriola, Laura; Andersson, Per-Olof; Evenepoel, Pieter; Gonzalez Oliva, Juan Carlos; Pisoni, Ronald; et al.
Abstract: Background and Aims: Oral cinacalcet (CIN) and IV-administered etelcalcetide (ETEL) are calcimimetics available for the management of secondary hyperparathyroidism (SHPT) in hemodialysis (HD) patients. This pilot study assessed patient adherence to calcimimetic therapy and calcimimetic preference of nephrologists and nurses based on adapted questionnaires. Method: A cross-sectional survey was conducted with HD patients currently using a calcimimetic, and nephrologists and dialysis nurses who prescribed/administered calcimimetic in 7 European countries (Belgium, France, Germany, Italy, Spain, Sweden and the United Kingdom). Patient questionnaires were adapted from the Medication Adherence Report Scale (MARS), the Beliefs about Medicines Questionnaire (BMQ-specific Necessity and Concern), and Treatment Intrusiveness Scale (TIS) to understand patterns of adherence and perceptions of medications; questions about gastrointestinal (GI) symptoms were included. Questionnaires for nephrologists and nurses were adapted from the Treatment Rating Scale (TRS), Health Professional Preference Scale (HPPS), and Prescribing Comparator Scale (PCS) to understand calcimimetic preference. Questionnaires were translated and administered in the local language. Results: Sixty HD patients (33 CIN and 27 ETEL), 16 nephrologists and 18 dialysis nurses participated in the survey. ETEL patients were younger than CIN patients (mean age: 57 vs. 59 yrs). ETEL patients also had a lower pill burden (mean no. of pills: 6 vs. 11) and had numerically fewer hospitalizations in the last 6 months (mean no. of days: 1.5 vs 3.9) than CIN patients. Self-reported adherence to CIN was high (mean MARS: 4.7±0.7). ETEL and CIN patients did not perceive medications (excluding dialysis, diet and dietary restrictions) as interfering with their life (mean TIS: 1.5±0.5 vs. 1.6±1.6) and neither calcimimetic group had a specific belief in medicines in terms of necessity (mean BMQ CIN: 2.4±0.6 and ETEL: 2.3±0.4) or concerns about potential side-effects (mean BMQ CIN: 3.1±0.6 and ETEL: 3.5±0.7). ETEL patients were less likely than CIN patients to experience GI symptoms in the prior month: nausea (11% vs. 49%), vomiting (11% vs. 24%), and diarrhea (15% vs. 33%). Overall, the adapted patient questionnaires showed good internal consistency for MARS (Cronbach's α=0.99) and BMQ-Necessity and BMQ-Concerns scales (CIN: α=0.74 and ETEL: α=0.81) but lower consistency for TIS (α=0.3 for both CIN and ETEL). Nephrologists and nurses had been practicing for a mean of 17 yrs. Nephrologists and nurses viewed ETEL to have more efficacy, lower risk of side effects, lower risk of non-adherence, lower burden for patients compared to CIN according to the TRS. According to HPPS, the top 3 treatment attributes for ETEL preference vs. CIN among nephrologists were encouraging patient adherence (93%; n=14/15), minimizing patient burden (87%; n=13/15) and having fewer side effects (80%; 12/15). Similar for nurses, encouraging patient adherence (88%; n=15/17) and minimizing patient burden (94%; n=16/17) were top attributes for ETEL preference as well as improving patient quality of life (82%; 14/17). Based on PCS, the majority of nephrologists agreed that compared to CIN, ETEL will ensure high adherence (100%), achieve better PTH control (93%; 14/15), reduce treatment burden for patients (87%; 13/15), improve patient's quality of life (80%; 12/15), and improve effectiveness without increasing side-effects (80%; 12/15); they also agreed that ETEL created more work for nursing staff (80%; 12/15). Two thirds of nephrologists (n=10/15) agreed that ETEL would be more efficacious than CIN. Conclusion: In this pilot study, CIN patients self-reported high adherence and both calcimimetic groups did not perceive medications to be concerning or intrusive. Nephrologists and nurses showed preference for ETEL than CIN. The questionnaires were validated and will be administered in a large study.